Relevansi Al-Hikam Ibnu ‘Athā’illāh bagi Pendidikan Akhlak Generasi Muda di Konteks Pascamodern - Akhmad Ali Said; Bayu Fermadi; Moch. Bashori Alwi; Misbachul Munir; Moh. Hasan Fauzi; Yuni Pangestutiani; Aina Noor Habibah; Siti Isti'anah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2022)
presents complex challenges to the moral and spiritual identity formation of youth. Conventional models of character education tend to rely on behavioral and secular frameworks, which often fail to adequately address the inner and spiritual dimensions of human development. This article aims to systematically examine the relevance and potential integration of Sufi teachings found in Al-Hikam by Ibn Ata’illah al-Sakandari as a transformative framework for youth character education within this context. This study employs a systematic literature review of fifty selected scholarly articles retrieved from major academic databases, including Consensus, Semantic Scholar, and PubMed, which met the established inclusion criteria. Thematic synthesis reveals that the core values articulated in Al-Hikam, such as ikhlas or sincerity, muhasabah or self reflection, tawadhu or humility, shabr or patience, and syukr or gratitude, are highly relevant for fostering resilience, self awareness, and moral responsibility among adolescents. The integration of these values through curricular strategies, experiential learning activities, and teacher modeling demonstrates positive and measurable impacts across three developmental domains, namely affective spiritual growth, moral and behavioral formation, and cognitive academic performance. However, the implementation of this integrative approach faces several challenges, including limited teacher preparedness, fragmented curricula, and methodological difficulties in assessing inner spiritual transformation. In conclusion, the teachings of Al-Hikam provide a strong and contextually relevant philosophical and pedagogical foundation for holistic character education in the midst of postmodern societal complexities. Effective implementation requires sustained commitment to integrative educational models, systematic capacity building for educators, and close collaboration among schools, families, and community environments.